The Effect of Pterygopalatine Fossa Block (PPFB) during Endoscopic Sinus Surgery (ESS) on Intraoperative Bleeding: A Randomized Control Trial - Paudel, Deepak; Chettri, S.T.; Shah, S.P.; Shah, B.P.; Manandhar, S.; Mishra, S. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Bleeding is the frequent intraoperative complication in most of the surgeries and remains a challenge for the surgeons and anesthesiologists. Major blood loss during FESS is rare but even a small amount of bleeding disturbs the endoscopic surgery field, increases the likelihood of complications, lengthens the time of surgery and results in incomplete surgery. The greater palatine canal (GPC) local injection is used to limit posterior bleeding during sinus surgery. Objective: To study the effect of pterygopalatine fossa block on intraoperative bleeding and operative field optimization during endoscopic sinus surgery. Methods: Prospective double blind randomized control trial. Thirty six patients were recruited in the study who also acted as their own control. PPFB was done only on one side of the nostril and the side was randomized by the lottery; neither the patient nor the operating surgeons were aware of the laterality. Boezaart score was used to quantify the intra-operative blood loss. Results: Blood loss between block group and non-block group was compared. Patients in block group had more stable hemodynamics with no fluctuations, better visibility of the surgical field and decreased blood loss as compared with non-block group. Conclusion: Greater palatine fossa block is a useful adjunct in patients undergoing endoscopic sinus surgery. It provided more stable hemodynamics, good operative conditions by lowering blood loss.